2019
DOI: 10.1108/bfj-04-2019-0291
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ perceptions of wine tourism on the rural destinations development

Abstract: Purpose The purpose of this paper is to study the impact of wine tourism on rural destination development. Consequently, this study attempts to develop contemporary insights on this under-researched area such as residents’ perceptions of wine tourism and its impact on the rural destination development. Design/methodology/approach In this study, the authors used a structured survey questionnaire from a random sample of 318 respondents based on the Fruška Gora Mountain in Serbia. Research also used structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 72 publications
(139 reference statements)
0
33
0
3
Order By: Relevance
“…In this regard, the novel nature of this work is highlighted in line with the most recent approaches, since the literature review reveals the limited availability of conceptual and analytical frameworks to facilitate the understanding of the various aspects surrounding the issue of sustainability in relation to wine tourism [2,29], according to the residents' perspective [28,34,35]. The intention is thus to provide a reference to fill the gap in knowledge regarding industrial tourism by analyzing the relationship with sustainable tourism from the perspective of local residents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the novel nature of this work is highlighted in line with the most recent approaches, since the literature review reveals the limited availability of conceptual and analytical frameworks to facilitate the understanding of the various aspects surrounding the issue of sustainability in relation to wine tourism [2,29], according to the residents' perspective [28,34,35]. The intention is thus to provide a reference to fill the gap in knowledge regarding industrial tourism by analyzing the relationship with sustainable tourism from the perspective of local residents.…”
Section: Introductionmentioning
confidence: 99%
“…It must therefore be stressed that the sustainability of a tourism destination is a key element in improving competitiveness and contributing to the enhancement of the value of existing resources by boosting a region's economic and social evolution. In this sense, adopting sustainable practices as a form of differentiation in the market is a growing trend [27,28], but it is also growing as a need for business innovation [2,8,29], including the tourist area, among wineries.…”
Section: Introductionmentioning
confidence: 99%
“…Rittichainuwat et al (2008) investigated first-time and repeat tourists to Thailand and found significant differences in travel motivations among travelers with different demographic profiles and the significance of positive impressions of good food value (Velissariou and Vasilaki, 2014). Vukovic et al (2019) in their study determined the economic, socio-cultural and environmental importance of wine tourism, which create a positive image of the destination.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many cities in Serbia have specific gastronomy, but Novi Sad has been known by multiple and different foods and catering facilities, connecting many different cultures and minorities and nations. People create content themselves on Instagram and other social networks (Vukovic et al , 2019; Gajić et al , 2019). Through Instagram, they not only advertise their position in the society but directly present the facility where they received a serving of perfectly served food.…”
Section: Introductionmentioning
confidence: 99%